The da-da-de-da-da code - Rankin, Robert, 1949- (London : Gollancz, Orion Publishing Group, 2009)
All Jonny Hooker has to do to claim a big prize is to solve the Da-Da-De-Da-Da Code. Scattered throughout popular music, Jonny knows the code has something to do with the Devil's Chord, as well as the great blues musician Robert Johnson; Elvis Presley--who is of course still alive--and with the Secret Parliament of Five, who dictate world affairs. When he solves the Code, Jonny will discover why all the most famous rock musicians die at 27, the truth about raising an ancient god, and all about the destruction of the world.
Keywords: Musicians -- Fiction; Humorous stories